Epigenetic DNA Demethylation Causes Inner Ear Stem Cell Differentiation into Hair Cell-Like Cells - Zhou, Yang; Hu, Zhengqing (Frontiers in Cellular Neuroscience, 2016)
The DNA methyltransferase (DNMT) inhibitor 5-azacytidine (5-aza) causes genomic demethylation to regulate gene expression. However, it remains unclear whether 5-aza affects gene expression and cell fate determination of stem cells. In this study, 5-aza was applied to mouse utricle sensory epithelia-derived progenitor cells (MUCs) to investigate whether 5-aza stimulated MUCs to become sensory hair cells. After treatment, MUCs increased expression of hair cell genes and proteins. The DNA methylation level (indicated by percentage of 5-methylcytosine) showed a 28.57% decrease after treatment, which causes significantly repressed DNMT1 protein expression and DNMT activity. Additionally, FM1-43 permeation assays indicated that the permeability of 5-aza-treated MUCs was similar to that of sensory hair cells, which may result from mechanotransduction channels. This study not only demonstrates a possible epigenetic approach to induce tissue specific stem/progenitor cells to become sensory hair cell-like cells, but also provides a cell model to epigenetically modulate stem cell fate determination.